Use of Silica Tubes as Nanocontainers for Corrosion Inhibitor Storage - Cesia Ávila-Gonzalez; Rodolfo Cruz-Silva; Carmina Menchaca; Selene Sepulveda-Guzman; Jorge Uruchurtu (Journal of Nanotechnology)
A new alkyd paint anticorrosion smart coating was developed by using silica nanoparticles as corrosion inhibitor nanocontainers. Silica particles were mixed with the paint at different concentrations to study their performance and ensure their free transportation to the damaged metal. The filling up of silica particles was done preparing three solutions: distilled water, acetone, and a mixture of both, with Fe(NO3)3 and silica particles immersed in each of the solutions to adsorb the inhibitor. Acetone solution was the best alternative determined by weight gain analysis made with the inhibitor adsorbed in silica nanocontainers. Steel samples were painted with inhibitor silica nanocontainer coatings and immersed in an aqueous solution of 3% sodium chloride. Polarization curves and electrochemical noise techniques were used to evaluate the corrosion inhibitor system behavior. Good performance was obtained in comparison with samples without inhibitor nanocontainer coating.